Effect of hot rolling on microstructure and properties of high-chromium cast iron hardfacing cladding plate. (14th December 2018) - Li, Yanwei; Li, Yugui; Han, Peisheng; Wang, Xiaogang
Abstract: In this study, a high-chromium cast iron (HCCI) material hardfacing on a low-carbon steel (LCS) plate is fabricated into a symmetrical sandwich structure, which is subjected to multi-pass hot rolling on a rolling mill at a reduction of 15%, 25%, and 35%. The effects of different rolling reductions on the microstructure (interface and HCCI layer) and mechanical properties (bonding strength, hardness, and wear resistance) of the composite sheets are studied. Results show that the cracks in the hardfacing layer disappear. HCCI and LCS exhibit coordinated thermal deformation, and the shape of the composite plate after hot rolling is good without warpage. HCCI/LCS composite panels are successfully prepared. As the rolling reduction increases, the microstructure defects at the original bonding interface are eliminated. Moreover, a carbide-free zone and intergrowth are observed, and the bonding strength increases. Hot rolling results in the breakdown of a eutectic carbide chain network of hardfacing HCCI cast iron layer and the dispersion distribution of carbides. The precipitation of secondary carbides is observed in the HCCI layer after hot rolling at 35%, which results in increased hardness of HCCI.